Mechanical behaviour of frozen soils under triaxial compression - Neuber, H.; Wolters, R.; National Research Council of Canada. Division of Building Research (National Research Council of Canada, 1977)
Stability of artificially frozen coal mining shafts in Germany has initiated interest in the mechanical properties of frozen ground. This article reports on laboratory uniaxial and triaxial loading tests on frozen soil samples taken from several geologicial zones through which a shaft has been driven. The effects of such factors as grain size, ambient pressure, temperature and rate of loading on the strength and deformation properties of frozen soils were investigated. Peer reviewed: No NRC publication: Yes